PENYULUHAN SISTEM AGRIBISNIS SUATU PENDEKATAN HOLISTIK - NYOMAN SUPARTA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
The rising issues nowadays related to the existence of chicken broiler business andagribusiness system are low added value obtained for farmers, disharmonic relationship amongagribusiness system agents, and low competitive ability. On the other hand, the business andagribusiness system improvement need dynamic, creative and innovative human recourses with strongbusiness instinct, and the ability in understanding the ethics of agribusiness system relationship wellfor achieving better business results. The reason of this gap might be caused by the fact that thefarmers or other agribusiness sub-system agents do not fully understand the business and agribusinesssystem. The research has been carrying out to obtain depiction of agribusiness behavior withindustrial culture, and its extension approach. The result of the research shows that application of theholistic extension of agribusiness was needed. The extension‘s objective exactly to the change ofagribusiness behavior with industrial culture. The extension materials include all of productiontechnical aspect, agribusiness management aspect, and agribusiness system relationship managementaspect with industrial’s perception, so the agribusiness system businessmen’s could have the sameperception and attitude about: vision, missions, business ethics, objective, goal and cooperative planwitch formulated with open way. The extension methods must be more varieties. The extensionagribusiness system needs professionalism extensionists too, but usually base on the basic philosophyand principles of the extension.